Antioxidant and anti-inflammatory properties of ginsenoside Rg1 for hyperglycemia in type 2 diabetes mellitus: systematic reviews and meta-analyses of animal studies - Xie, Qian; Zhang, Xiaoran; Zhou, Qian; Xu, Yumei; Sun, Lisha; Wen, Qing; Wang, Wei; Chen, Qiu (Frontiers in Pharmacology, 2023)
Background: According to the existing laboratory data, ginsenoside rg1 may help cure diabetes and its complications by reducing oxidative stress and managing inflammation. However, this conclusion lacks reliability and is unclear. As a result, the purpose of this systematic review and meta-analysis was to evaluate the antioxidant and anti-inflammatory effects of ginsenoside rg1 in the treatment of diabetes and its complications. Methods: We searched for relevant studies published through December 2022, including electronic bibliographic databases such as PubMed, EMBASE and Web of Science, CNKI and Wanfang. SYRCLE's Rob tool was used to conduct meta-analysis to assess the methodological quality of animal research. The meta-analysis was conducted using RevMan5.4 software following the Cochrane Handbook for Systematic Reviews of Interventions. This study is registered in the International Systems Review Prospective Registry (PROSPERO) as CRD42023386830.Results: Eighteen eligible studies involving 401 animals were included. Ginsenoside rg1 was significantly correlated with blood glucose (BG), insulin levels, body weight, superoxide dismutase (SOD), malondialdehyde (MDA), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) levels. In addition, according to subgroup analysis, the hypoglycemic, anti-inflammatory and antioxidant effects of ginsenoside rg1 in type 2 diabetic animals were not affected by experimental species, modeling, experimental drug dosage, and course of treatment.This meta-analysis presents a summary of the hypoglycemic effects of ginsenoside rg1, which are achieved through anti-inflammatory and antioxidant mechanisms. The findings provide evidence-based support for the medical efficacy of ginsenoside rg1. Specifically, ginsenoside rg1 reduced MDA levels and restored SOD activity to exert its antioxidant activity and had a positive effect on the reduction of IL-6 and TNF-α levels. However, the inclusion of studies with low methodological quality and the presence of publication bias may undermine the validity of the results.Further investigation with more rigorous experimental design and comprehensive studies is necessary to fully understand the specific glycemic mechanisms of ginsenosides.